Effects of Varenicline on Ethanol- and Food-Maintained Responding in a Concurrent Access Procedure - Ginsburg, Brett C.; Lamb, Richard J. (Alcoholism, clinical and experimental research, 2013)
Background Varenicline has been reported to reduce drinking in smokers and to selectively decrease responding for ethanol (EtOH) versus alternatives in preclinical studies. Such selectivity may reflect potential therapeutic effects and the involvement of nicotinic receptors in EtOH reinforcement. However, these studies have been conducted with EtOH and an alternative available in isolation or in separate groups, and selectivity can depend on the context in which reinforcement occurs. Whether varenicline selectivity is maintained when EtOH and an alternative are concurrently available has not been reported. To examine the effects of varenicline on EtOH self‐administration when an alternative is concurrently available, male Lewis rats (n = 5) were trained to respond for EtOH and food under a concurrent FR5 FRX schedule where the fixed ratio (FR) for food was adjusted (FR = 25 or 35 for each subject) to provide similar numbers of EtOH and food deliveries during a 30‐minute session. Methods Doses of varenicline (0.56 to 5.6 mg/kg, i.p.) or vehicle were administered 30 minutes before sessions. Effects of varenicline on responding across the session and during each tenth of the session were compared to responding following vehicle treatment. Results Lower doses (0.56 to 1.0 mg/kg) of varenicline increased responding for EtOH without affecting responding for food. Higher doses disrupted responding for EtOH and food similarly. Conclusions Previous reports of varenicline selectivity on EtOH‐maintained responding do not generalize to other experimental conditions such as a concurrent schedule. The increase in responding for EtOH following lower doses might be due to enhanced EtOH reinforcement, decreased food reinforcement, rate dependency, or greater perseverance on the initial, EtOH response.